Musicoterapia Como Alternativa De Intervención Para La Ansiedad y Depresión En Adultos: Una Revisión De Estudios Años 2012 - 2022 En Latinoamérica y España. (2022)
This work focuses on music therapy as an alternative intervention for anxiety and depression in adults based on studies carried out in Latin America and Spain in a period from 2012 to 2022. The objective is to describe the results of scientific studies carried out on of the use of music therapy as an alternative for the intervention of anxiety and depression in adults. Regarding the methodology, a qualitative/descriptive systematic review was carried out, for which 24 investigations that met the proposed search criteria were selected, and refined using the Prisma methodology and a search log. This research concludes by validating the information consulted in which it is stated that music therapy is an excellent intervention alternative for anxiety, but as an intervention for depression, more research is needed to reach a more accurate conclusion because the results are contradictory among some researchers